O PROGRAMA NAVEGAPARÁ COMO POLÍTICA PÚBLICA DE INCLUSÃO DIGITAL: IMPLICAÇÕES NAS ESCOLAS PÚBLICAS DO ESTADO DO PARÁ - Prazeres, Maria Sueli Corrêa dos (2016)
The research analyzed the digital inclusion policy proposed by Program NAVEGAPARÁ for high schools in the metropolitan area of Belém/Pará. This study aimed to identify the contradictions between the legal speech and the effectiveness of the program in the social and educational practice. By bringing out the discourse of “digital inclusion” and “democratization of access” as axes underlying the program, it intends to identify the possibilities and the limits of the program´s effectiveness, considering the empirical reality that places the object of analysis. Also aimed to identify the concepts that underlie the program, as well as its implications in the school fields. It was adopted as theoretical framework the historical materialism, contextualizing the entire scenario of digital inclusion policies in Brazil and in the Amazon, considering the contradictions inherent in the educational policies in capitalist society. This approach takes as base Marx, Mészáros, Vieira Pinto, and other authors who discuss the same strand. The uniqueness of the program NAVEGAPARÁ is presented and analyzed through data collection instruments, using a semi-structured interview with representatives of both Program NAVEGAPARÁ/Infocentros and the Educational Technology Center, school coordinators, teachers placed in the computer lab, managers and teachers in general; questionnaires with 200 students and analysis of documents that provide the legal basis for the program. The Analyses show that the political conception of the program NAVEGAPARÁ is linked to the macroeconomic context of capitalist policies, led by the World Summit on the Information Society that guides governments and countries to work the digital inclusion as a way to promote social inclusion. Incorporating these guidelines, the program under review, is providing opportunities for access to digital resources in order to link the counties and government institutions, aiming to perform the digital inclusion. It is observed however, that from the point of view of the "democratization of access", although this process has advanced, cannot be effective as a totality. On the one hand, one cannot deny that not occur inclusion. However, this process has materialized in a precarious and limited way because of structural and technological conditions (obsolescence of computers, lack of equipment maintenance and poor quality of the internet connection); the instrumental conception underlying the digital inclusion policy and fragile formation for the appropriation of technological resources, which prevents be made effective the digital inclusion to the lines proposed by the program. On the other, it was also shown the subject´s willingness to assign new meanings to digital technologies in schools, although the empirical reality imposes limits.